Characteristics of Zinc Deposits of North America (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1918)
H. A. BUEHLER, Rolla, Mo. -I consider the lead .and zinc deposits of the Mississippi Valley to be the result of descending waters. There are many features that we have not determined and yet when you see the general field relations, it seems to me that the cause and effect can be well explained by descending circulation. In the Joplin-Miami district, for instance, the ore deposits are connected with openings or with old cavity fillings which have a direct connection downward from the surface to practically 300 ft. In the Miami camp, in the western part of the field, some of the deepest orebodies are directly connected with water, channels; the same condition has been obvious and always present with the shallower ores. I speak of one deposit that I have examined more thoroughly than any other in that district, the Admiralty property, which contains large openings or caves at the deepest levels. It seems to me that waters which would pass upward through 1800 ft. of dolomite would be saturated with lime and magnesia so far as the carbon dioxide of those waters would dissolve them, and therefore, on